UNCOVERing the Faint End of the z ∼ 7 [O iii] Luminosity Function with JWST’s F410M Medium Bandpass Filter - Isak G. B. Wold; Sangeeta Malhotra; James E. Rhoads; John R. Weaver; Bingjie Wang (The Astrophysical Journal)
Strong emission from doubly ionized oxygen is a beacon for some of the most intensely star-forming galaxies. JWST enables the search for this beacon in the early Universe with unprecedented sensitivity. Using UNCOVER DR1 JWST/NIRCam and Hubble Space Telescope (HST) imaging data of A2744, we identify strong (rest-frame EW > 500Å) [O iii ] _5008 emitters at z ∼ 7 based on excess F410M flux. We find N = 68 z ∼ 7 [O iii ] candidates, including N = 33 with deep HST coverage required to rule out lower-redshift interlopers (13.68 arcmin ^2 with F814W 5 σ depth >28 AB). Such strong emission lines can produce very red colors often misinterpreted as evidence for old, massive stellar populations, but are shown to be emission lines where we have spectra. Using this deep HST sample, we derive a new [O iii ] luminosity function (LF) spanning $41.1\lt {{\rm{log}}}_{10}(L/{{\rm{erg}}\,{\rm{s}}}^{-1})\lt 42.4$ , an order of magnitude deeper than previous z ∼ 6 studies. This LF is fit by a power law with a faint-end slope of $α =-2.0{7}_{-0.23}^{+0.22}$ . Our results are consistent with the z ∼ 7 FRESCO [O iii ] LF across the overlapping 0.5 dex range, $41.9\gt {{\rm{log}}}_{10}(L/{{\rm{erg}}\,{\rm{s}}}^{-1})\gt 42.4$ . Combining both data sets, we construct an LF spanning 2 dex in luminosity, with a best-fit Schechter function: $α =-2.1{3}_{-0.16}^{+0.15}$ , ${{\rm{log}}}_{10}({φ }^{* }/{{\rm{Mpc}}}^{-3})=-4.1{7}_{-1.39}^{+0.49}$ , and ${{\rm{log}}}_{10}(L^{* }/$ erg s ${}^{-1})=43.0{6}_{-0.29}^{+0.90}$ . There is little evolution between this LF and published [O iii ] LFs at 3 < z < 8, and no evidence of a turnover at faint luminosities. The sizes of these extreme [O iii ] emitters are similar to their low redshift counterparts, the Green Peas. The z ∼ 7 [O iii ] LF aligns with the Ly α LF at the bright end, suggesting many of these galaxies are also Ly α emitters.